Age‐dependent changes in the reproductive axis responsiveness to kisspeptin‐10 administration in healthy men. (27th December 2018) - Ullah, Hamid; Nabi, Ghulam; Zubair, Hira; Ullah, Rahim; Shahab, Muhammad
Abstract: The present study was designed to assess the responsiveness of hypothalamic–pituitary–gonadal axis to kisspeptin administration with increasing age in men. Human kisspeptin‐10 was administered in single iv bolus dose (1 µg/kg BW) to healthy adult, middle and advanced age men. Serial blood samples were collected for 30 min pre‐ and 120 min post‐kisspeptin injection periods at 30‐min interval. Analysis of plasma LH by ELISA showed a significant ( p < 0.05) increase after kisspeptin‐10 administration in all groups, whereas plasma testosterone concentration was significantly elevated ( p < 0.05) after kisspeptin‐10 injection only in the adult men group. Present results suggest that in men, central hypothalamic–pituitary axis remains active and shows responsiveness to kisspeptin stimulation across life. However, Leydig cell responsiveness to kisspeptin‐induced LH decreases with age in men.